2001
DOI: 10.1074/jbc.m108482200
|View full text |Cite
|
Sign up to set email alerts
|

The Peroxisome Proliferator-activated Receptor δ Promotes Lipid Accumulation in Human Macrophages

Abstract: The peroxisome proliferator-activated receptors (PPARs) are a family of fatty acid-activated transcription factors which control lipid homeostasis and cellular differentiation. PPAR␣ (NR1C1) controls lipid oxidation and clearance in hepatocytes and PPAR␥ (NR1C3) promotes preadipocyte differentiation and lipogenesis. Drugs that activate PPAR␣ are effective in lowering plasma levels of lipids and have been used in the management of hyperlipidemia. PPAR␥ agonists increase insulin sensitivity and are used in the m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
156
0
3

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 250 publications
(165 citation statements)
references
References 49 publications
6
156
0
3
Order By: Relevance
“…ND indicates not detected; C18:3n-6/C18:2n-6, ⌬6 desaturase index; C20:4n-6/C20:3n-6, ⌬5 desaturase index. PPAR␥ in liver and adipose tissue, respectively, 39,40 and by PPAR␦ in macrophages 41 and skeletal muscle, 42 underscoring the complexity of the PPAR system in which the responses to a certain ligand may differ between different cell types and tissues. Several studies have suggested antiinflammatory effects after PPAR␣ 14,15 and PPAR␥ activation, 16 although the antiinflammatory properties of PPAR␥ are more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…ND indicates not detected; C18:3n-6/C18:2n-6, ⌬6 desaturase index; C20:4n-6/C20:3n-6, ⌬5 desaturase index. PPAR␥ in liver and adipose tissue, respectively, 39,40 and by PPAR␦ in macrophages 41 and skeletal muscle, 42 underscoring the complexity of the PPAR system in which the responses to a certain ligand may differ between different cell types and tissues. Several studies have suggested antiinflammatory effects after PPAR␣ 14,15 and PPAR␥ activation, 16 although the antiinflammatory properties of PPAR␥ are more controversial.…”
Section: Discussionmentioning
confidence: 99%
“…The PPAR␦ ligand GW501516 was reported to increase expression of ABCA1 and induce apoAI-specific cholesterol eff lux from human THP-1 cells. Vosper et al (37) showed that another PPAR␦ ligand induced expression of scavenger receptors (SR-A and CD36) involved in lipid accumulation in macrophages. We observed no changes in LXR␣, ABCA1, ABCG1, or CD36 expression in aorta or peritoneal macrophages after GW0742 treatment (data not shown).…”
Section: Discussionmentioning
confidence: 99%
“…More recently, expression has been reported on hepatocytes under certain circumstances (Vosper, et al, 2001,Yu, et al, 2001,Zhou, et al, 2006 and smooth muscle cells (Lim, et al, 2006,de Oliveira Silva, Delbosc, Arais, Monnier, Cristol, & Pares-Herbute, 2006, Kwok, Juan, and Ho, 2006. CD36 plays a role in uptake of apoptotic cells (Savill, Hogg, Ren, and Haslett, 1992), shed photoreceptor outer segments , and modified lipoproteins (Endemann, Stanton, Madden, Bryant, White, & Protter, 1993,Podrez, et al,2000, and in recognition of ligands that trigger an innate immune response, including components of gram positive bacteria cell walls (Hoebe, et al, 2005,Stuart, et al, 2005 (as a co-receptor with Toll Like Receptor (TLR) 2), fibrillar amyloid β (Bamberger, Harris, McDonald, Husemann, & Landreth, 2003,El Khoury, et al, 2003, which is a constituent of Alzheimer plaque, and resembles fibrillar amyloid protein (Medeiros, et al, 2004), that may occur in atherosclerotic plaque.…”
Section: Cd36 Structure and Expressionmentioning
confidence: 99%